Answers

Solutions by everydaycalculation.com

Everydaycalculation.com » Answers » Solve for x

Solve 6x - 1 = 4x + 6

How to solve 6x - 1 = 4x + 6? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.

Steps for finding the solution

We have 6x - 1 = 4x + 6

First, we move the x terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:
i) Adding 1 to both sides
ii) Subtracting 4x from both sides

Therefore, 6x - 4x = 6 + 1

or, 2x = 7

Next, divide both sides by 2, which is the coefficent of x

Note: if a = b, then a ÷ c = b ÷ c

2x/2 = 7/2

x = 7/2 or, x = 3.5

Solve another equation

𝒙 =

Related

© everydaycalculation.com